Production of Curved Surface Composites Reinforced with Rubber Layer - Albayrak, Mustafa; Kaman, Mete Onur (My University, 2021)
In this study, laminated composites reinforced with rubber layers were produced under vacuum infusion method for different curved surface geometries. For this purpose, EPDM rubber interlayers, known for their impact-absorbing feature, were laid on curved-surface metal molds processed on computer numerical control (CNC) benches together with woven glass fiber woven fabrics. Thus, sandwich plates with an array of [0 °] 6 glass fiber / EPDM rubber / [0 °] 6 glass fiber were obtained. It has been evaluated how the interface adhesion pr operties of the structure, which is formed by combining different types of materials under vacuum, depending on the temperature curing. For this reason, composites were produced by curing under high temperature and room temperature. As a result, it was determined that in composites produced by curing at room temperature, separation occurred between layers and the desired interface toughness could not be achieved. However, no delamination defects were observed in the structure of sandwich plates obtained for 100 ° C curing, and it was observed that the adhesion tendency of rubbers with hyper-elastic material structure increased with temperature. A good harmony was achieved between fabrics and rubbers with the effect of temperature together with vacuum and very smooth geometries were obtained.
Keywords: Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kompozitler